Cutting Edge: Probiotics and Fecal Microbiota Transplantation in Immunomodulation - Wenjie Zeng; Jie Shen; Tao Bo; Liangxin Peng; Hongbo Xu; Moussa Ide Nasser; Quan Zhuang; Mingyi Zhao (Journal of Immunology Research)
Probiotics are commensal or nonpathogenic microbes that confer beneficial effects on the host through several mechanisms such as competitive exclusion, antibacterial effects, and modulation of immune responses. Some probiotics have been found to regulate immune responses via immune regulatory mechanisms. T regulatory (Treg) cells, T helper cell balances, dendritic cells, macrophages, B cells, and natural killer (NK) cells can be considered as the most determinant dysregulated mediators in immunomodulatory status. Recently, fecal microbiota transplantation (FMT) has been defined as the transfer of distal gut microbial communities from a healthy individual to a patient’s intestinal tract to cure some immune disorders (mainly inflammatory bowel diseases). The aim of this review was followed through the recent literature survey on immunomodulatory effects and mechanisms of probiotics and FMT and also efficacy and safety of probiotics and FMT in clinical trials and applications.